The role of ambulatory blood pressure monitoring in enhancing medication adherence among patients with newly diagnosed hypertension: an analysis of the National Health Insurance cohort database - Hack-Lyoung Kim; So-Jeong Park; Yoon-Jong Bae; Sang Hyum Ihm; Jinho Shin; Kwang-Il Kim (Clinical Hypertension, 2024)
Abstract Background Improving adherence to antihypertensive medication (AHM) is a key challenge in hypertension management. This study aimed to assess the impact of ambulatory blood pressure monitoring (ABPM) on AHM adherence. Methods We utilized the Korean National Health Insurance Service database. Among patients newly diagnosed with hypertension who started AHM between July 2010 and December 2013, we compared clinical characteristics and adherence between 28,116 patients who underwent ABPM prior to starting AHM and 118,594 patients who did not undergo ABPM. Good adherence was defined as a proportion of days covered (PDC) of 0.8 or higher. Results The total study population was 146,710, with a mean age of 50.5 ± 6.4 years; 44.3% were female. Co-morbidities were noted in 4.2%. About a third of patients (33.1%) showed good adherence. The ABPM group had a notably higher PDC (total PDC: 0.64 ± 0.35 vs. 0.45 ± 0.39; P < 0.001), irrespective of the number of medications, dosing frequency, or prescription duration. After adjusting for significant clinical variables, ABPM was still closely linked with good adherence (odds ratio, 2.35; 95% confidence interval, 2.28–2.41; P < 0.001). Conclusions In newly diagnosed hypertension, undergoing ABPM prior to AHM prescription appears to enhance adherence to AHM. The exact mechanisms driving this association warrant further exploration. Graphical Abstract